A Dendrite‐Free Lithium/Carbon Nanotube Hybrid for Lithium‐Metal Batteries - Wang, Zhi Yong; Lu, Zhong Xu; Guo, Wei; Luo, Qin; Yin, Yan Hong; Liu, Xian Bin; Li, Ye Sheng; Xia, Bao Yu; Wu, Zi Ping (Advanced materials (Weinheim), 2021)
Lithium (Li) metal is promising in the next‐generation energy storage systems. However, its practical application is still hindered by the poor cycling performance and serious safety issues for the consequence of dendritic Li. Herein, a dendrite‐free Li/carbon nanotube (CNT) hybrid is proposed, which is fabricated by direct coating molten Li on CNTs, for Li‐metal batteries. The favorable thermodynamic and kinetic conditions are the powerful force to drive the rapid lift upwards and infusion of molten Li into CNTs network, which is the key to form a uniform metallic layer in Li/CNTs hybrid. The obtained hybrid indicates super‐stable functions even at an ultrahigh current density of 40 mA cm−2 for 2000 cycles with a stripping/plating capacity of 2 mAh cm−2 in symmetric cells. Subsequently, this hybrid also demonstrates a significantly decreased resistance, excellent cycling stability at high current density and flexibility in the full Li‐S battery. This work provides valuable concepts in fabricating Li anodes toward Li‐metal batteries and beyond for their high‐level services. A dendrite‐free Li/carbon nanotube (CNT) hybrid is fabricated by direct coating of molten Li on CNTs for Li‐metal batteries. Favorable thermodynamic and kinetic conditions are a powerful force to drive the rapid lift upward and infusion of molten Li into CNTs network. The obtained hybrid exhibits superstable function even at an ultrahigh current density.